Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

The Chain Rule

  • Page ID
    625
  •  

    \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

    \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

    Our goal is to differentiate functions such as

    \[  y = (3x + 1)^{10}  \]

    The last thing that we would want to do is FOIL this out ten times. We now look for a better way.

    Definition: The Chain Rule

    If  \(  y = y(u) \) is a function of  \(u\), and \(u = u(x)  \) is a function of \(x\) then \[\dfrac{dy}{dx} = \dfrac{dy}{du} \dfrac{du}{dx} \]

    In our example we have

    \[         y = u^{10} \]

    and

    \[  u = 3x + 1 \]

    so that

    \[\dfrac{dy}{dx} = \dfrac{dy}{du} \dfrac{du}{dx} \]

            = (10u9)(3) = 30(3x+1)9

     

    Proof: Chain Rule

    Recall an alternate definition of the derivative:

    Example 2

    Find f '(x) if

    \[ f(x) = (x^4 - 3x^3 + x)^5 \]

    Solution

    Here

    \[  f(u) = u^20 \]

    and

    \[ u(x) = x^3 - x + 1 \]

    So that the derivative is

    \[  (20u^{19})(3x^2 - 1)  =  \left[20(x^3 - x + 1)^{19}\right](3x^2 - 1) \]

    Example 3

    Find f '(x) if

    \[ f(x) = (x^3 - x + 1)^{20} \]

    Solution

    Here

    \[ f(u) = u^5 \]

    and

    \[ u(x) = x^4 - 3x^3 + x \]

    So that the derivative is

    (5u4)(4x3 - 9x2 + 1)  =  [5(x4 - 3x3 + x)4](4x3 - 9x2 + 1)

    Example 4

    Find f '(x) if

    \[ f(x) = (1 - x)^9 (1-x^2)^4 \]

    Solution

    Here we need both the product and the chain rule.  First the product rule  

    f '(x) = [(1 - x)9][(1 - x2)4] ' + [(1 - x)9]' [(1 - x2)4]

    Now compute

    [(1 - x2)4]' = [4(1 - x2)3](-2x)

    and

    [(1 - x)9]'  = [9(1 - x)8](-1)

    Putting this all together gives

            f '(x) = [(1 - x)9][4(1 - x2)3](-2x) - [9(1 - x)8] [(1 - x2)4]

    Example 5

    Find f '(x) if

    \[ f(x)= \dfrac{ (x^3 + 4x - 3)^7}{  (2x - 1)^3} \]

    Solution

    Here we need both the quotient and the chain rule.

    \[ f'(x) = \dfrac{(2x - 1)^3\left[(x^3 + 4x - 3)^7\right]' - (x^3 + 4x - 3)^7 \left[(2x - 1)^3\right]'}{(2x - 1)^6} \]

    We first compute

    [(x3 + 4x - 3)7]' = [7(x3 + 4x - 3)6](3x2 + 4)

    and

    [(2x - 1)3]'  = [3(2x - 1)2](2)

    Putting this all together gives

    \[  f](x) = \dfrac{7(2x - 1)^3(x^3 + 4x - 3)^6(3x^2 + 4) + 6(x^3 + 4x - 3)^7 (2x - 1)^2}{  (2x - 1)^6 } \]

    Exercise

    Find the derivative of

    \[ f(x)= \dfrac{x^2(5 - x^3)^4 }{3 - x} \]       

    Contributors